Quality of Life and Functional Independence of Hip Fracture Patients: Data from a Single Center Follow-Up Study in Sri Lanka - Thilina Abeygunasekara; Sarath Lekamwasam; Janaka Lenora; Gayani Alwis (Annals of Geriatric Medicine and Research, 2021)
Background Data on the functional outcomes of hip fracture patients in Sri Lanka are limited. As this information is required for the design of long-term care plans, we assessed the physical activities (activities of daily living [ADL]) and quality of life (QoL) of hip fracture survivors in Sri Lanka. Methods A group of 180 consecutive patients with incident hip fractures admitted to a tertiary care center in Southern Sri Lanka were followed up for 12 months. The Sinhala versions of the Barthel Index, 36-Item Short-Form Survey, and Mini-Mental State Examination were used to assess ADL, QoL, and mental status, respectively. Results Of the 180 patients (149 women), 107 underwent surgery. An initial sharp decline and partial recovery of ADL and QoL were observed among patients with hip fractures. Furthermore, patients who underwent surgical treatment showed faster recovery of ADL and QoL than did patients who were managed conservatively. Similarly, patients who did not have complications during the hospital stay showed faster recovery of ADL and QoL than did patients with one or more complications. Conclusions Hip fractures profoundly affected both ADL and QoL, and recovery remained incomplete at 12 months post fracture. Patients who underwent surgery had a faster recovery than did patients who did not undergo surgery; similarly, patients without complications also had a faster recovery than did those with complications.